(untitled) (Revista Brasileira Multidisciplinar, 2021)
Binge eating has been seen as an increasing condition, mainly among overweight and obese individuals. However nutritional interventions prescribed to these individuals commonly impose food restrictions, which could trigger binge eating episodes. Therefore this study aimed to investigate the existence and effectiveness of ‘non-diet’ nutritional interventions for treatment of binge eating. As a bibliographic review, studies between 2007 and 2017 that ‘non-diet’ nutritional interventions and evaluated their effectiveness for binge eating between 2007 and 2017 were included in this study. Eighteen met the inclusion criteria, and they conducted interventions based on Intuitive Eating, Health at Every Size, Mindful Eating, Eating Competence and other interventions classified as ’non-diet’. In all of them there was a significant reduction in binge eating episodes, and also improvements in other aspects of eating behavior and eating consumption. Although the studies conducted different interventions, interestingly they have similarities, such as respecting the signs of hunger and satiety and breaking of the mentality of food restriction, which both, in agreement with several authors, may be at the heart of the effectiveness of these interventions. Thus it is suggested that ’non-diet’ nutritional interventions are promising for the treatment of binge eating.